THE INFLUENCE OF SEXUAL STEREOTYPES ON SOCIAL FUNCTIONING OF MODERN YOUTH - Pototska, Iryna; Rysynets, Tetiana; Loiko, Liudmyla; Herasymuk, Valeriia (PSYCHOLOGICAL JOURNAL, 2019)
Sexual attitudes mean readiness, predisposition to certain sexual actions; an agent’s state of internal, unconscious readiness to form an attitude and to behave in a certain way with the objects of reality or with information about them. The norms of sexual behavior and, accordingly, sexual attitudes are changing radically in the last decades. Young people do not only become mature more early, but also earlier begin sexual life. Modern boys and girls gain sexual experience more early; these changes cover the entire cycle of psychosexual development and all forms of sexual behavior from masturbation to sexual intercourse. The research was organized at N.I. Pirogov National Medical University in Vinnitsia. The sample consisted of 108 people (from 18 to 26 years old). Male students were 92 people (20 of them were foreigners and 72 were Ukrainian students) and 36 respondents were female students. The empirical study was conducted using Eysenck Personality Questionnaire and the author’s sexual behavior questionnaire for students. The study results indicate a strongly negative attitude to immoral intimate relationships, a fairly serious attitude to intimacy, and respect for marriage. Modern sexual education does not allow students to fully understand all the positive and negative aspects of sexual relations. The data obtained indicate existing psychological barriers to casual sexual intercourses. The study of cross-cultural differences has revealed that Ukrainian students of both genders have a strongly negative attitude to sex without commitment. The surveyed foreigners showed the same ratio of loyal attitudes and strongly negative attitudes to depersonalized sex. The Ukrainian girls showed full confidence in their sexual partners. The Ukrainian men accept a dominant position in sexual relations. Most foreigners have problems with sexual life, it is difficult for them to control or suppress their impulses. The key factor determining sexual patterns is upbringing. The prevalence of Puritan elements contributes to formation of internal sexual prohibitions. There is a tendency when men accept feminine social roles, and women take masculine ones. A general low level of libido was revealed in the study.